The Food and Drug Administration and pragmatic clinical trials of marketed medical products. (October 2015) - Anderson, Monique L; Griffin, Joseph; Goldkind, Sara F; Zeitler, Emily P; Wing, Liz; Al-Khatib, Sana M; Sherman, Rachel E
Pragmatic clinical trials can help answer questions of comparative effectiveness for interventions routinely used in medical practice. Pragmatic clinical trials may examine outcomes of one or more marketed medical products, and they are heterogeneous in design and risk. The Food and Drug Administration is charged with protecting the rights, safety, and welfare of individuals enrolled in clinical investigations, as well as assuring the integrity of the data upon which approval of medical products is made. The Food and Drug Administration has broad jurisdiction over drugs and medical devices (whether or not they are approved for marketing), and as such, clinical investigations of these products are subject to applicable Food and Drug Administration regulations. While many pragmatic clinical trials will meet the criteria for an exemption from the requirements for an investigational new drug application or investigational device exemption, in general, all clinical investigations of medical products that fall under Food and Drug Administration jurisdiction must adhere to regulations for informed consent and review by an institutional review board. We are concerned that current Food and Drug Administration requirements for obtaining individual informed consent may deter or delay the conduct of pragmatic clinical trials intended to develop reliable evidence of comparative safety and effectiveness of approved medical products that are regulated by the Food and Drug Administration. Under current regulations, there are no described mechanisms to alter or waive informed consent to make it less burdensome or more practicable for low-risk pragmatic clinical trials. We recommend that the Food and Drug Administration establish a risk-based approach to obtaining informed consent in pragmatic clinical trials that would facilitate the conduct of pragmatic clinical trials without compromising the protection of enrolled individuals or the integrity of the resulting data.